RECONSTRUCTING RATIONALIZATION IN ISLAMIC EDUCATION: A Systematic Literature Review of Max Weber's Bureaucracy Theory - Widiastuty, Hesty; Hilmy, Masdar; Erawati, Desi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Max Weber's theory of rationalization and bureaucracy offers a critical framework for understanding organizational structures in Islamic education. However, the standardization inherent in bureaucratic systems often conflicts with the decentralized and value-driven nature of Islamic education. Purpose: This study explores the reconstruction of rationalization in Islamic education management through Weber's bureaucratic theory, analyzing how it can be harmonized with Islamic values. Method: A systematic literature review (SLR) was conducted, synthesizing research from databases such as Scopus, Web of Science, and Google Scholar. Result: The findings reveal that while Weberian bureaucracy, characterized by hierarchical authority and legal-rational procedures, enhances efficiency, it may also introduce rigidity that limits innovation and adaptability to modern challenges. This study proposes a balanced approach that integrates bureaucratic efficiency with Islamic ethical principles, emphasizing flexibility, value-based leadership, and cultural integration. Implication: The research provides valuable insights for policymakers and educational leaders seeking to modernize governance frameworks while preserving core Islamic values. It highlights the importance of adapting Weber's bureaucratic model to meet contemporary educational demands without compromising spiritual and moral integrity. Conclusion: The study concludes by advocating for an integrated approach that combines bureaucratic structures with Islamic values, fostering management systems that are both efficient and responsive. Future research should further explore the application of Weber's theory in Islamic education, focusing on leadership, cultural considerations, and the implications for governance and educational reform.